Investigation of future applications of self-engineering using drones. (2022) - Tahir Naz, Ayesha; Brooks, Sam; Roy, Rajkumar
Abstract: Self-engineering (SE) systems aim to autonomously respond to a loss of function and take action to return functionality. Recently there have been a number of demonstrations of SE using multi-rotor drones to inspect and repair systems (such as repairing potholes), though many of these systems do not meet all the requirements of a SE system. This research identifies and explores new ideas for SE where drones could be utilised. Five ideas were successfully identified from consultations with experts and authors. The five ideas created are: 1) self-repair in enclosed spaces of ships, 2) self-cleaning roads, 3) self-repairing air conditioning systems, 4) autonomous underwater pipe repair, and 5) self-repair of damaged building cladding. Possible inspection and repair actions that a drone could perform are identified for each proposed system. From a short industry survey and further interviews, idea 1) (self-repair in enclosed spaces) was identified as the most promising for future development. The potential cost of building the system is discussed at the end of the paper; however, detailed cost estimation is too uncertain because of the difficulty in estimating the cost of developing autonomous capabilities.